2002
DOI: 10.1046/j.1365-3083.2002.01075.x
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae Inhibits Apoptosis in Human Epithelial and Monocyte Cell Lines*

Abstract: Chlamydia pneumoniae is an obligate intracellular pathogen with a tendency to cause persistent infections that has been associated with many chronic conditions such as asthma and coronary artery disease. However, its immunopathogenic mechanisms are poorly understood. When aiming to study the impact of C. pneumoniae infection on host cell apoptosis, we found that epithelial infected (HL) cells and macrophages (U937‐line) were resistant to staurosporine and tumour necrosis factor (TNF)‐α‐induced physiological ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
34
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 47 publications
3
34
0
2
Order By: Relevance
“…Therefore, we concluded that the effect of M. fermentans is upstream of the mitochondria. This result is similar to a recent observation regarding the effect of Chlamydia pneumoniae infection, 23,24 which was reported to render epithelial and monocyte cell lines resistant to TNFainduced apoptosis, via blockage of mitochondrial cytochrome c release.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we concluded that the effect of M. fermentans is upstream of the mitochondria. This result is similar to a recent observation regarding the effect of Chlamydia pneumoniae infection, 23,24 which was reported to render epithelial and monocyte cell lines resistant to TNFainduced apoptosis, via blockage of mitochondrial cytochrome c release.…”
Section: Discussionsupporting
confidence: 92%
“…Only a few papers have been published regarding inhibition of TNFa-induced apoptosis by Chlamydia pneumonia 23,24 and Hepatitis C Virus. 25 These support the hypothesis 26 that parasite bacteria might use a mechanism to prevent host cell apoptosis, in order to promote their survival and replication.…”
Section: Discussionmentioning
confidence: 99%
“…C. pneumoniae-dependent proliferation of the host cell, as well as cell damage, may alter the structure and function of the lung. Several studies indicate that C. pneumoniae inhibits apoptosis of monocytes and epithelial cells (1,3,27). Our data support these findings and furthermore suggest that C. pneumoniae infection leads to increased proliferation in epithelial cells.…”
Section: Discussionsupporting
confidence: 90%
“…Several obligate intracellular bacteria [e.g. Chlamydia (Airenne et al, 2002;Fan et al, 1998;Geng et al, 2000;Perfettini et al, 2002), Rickettsiae (Clifton et al, 1998)] and protozoa [T. gondii (this study) (Goebel et al, 1998;Goebel et al, 1999;Goebel et al, 2001;Nash et al, 1998), Theileria spp. Heussler et al, 1999;Heussler et al, 2001)] actively suppress host apoptosis.…”
Section: Discussionmentioning
confidence: 80%